2021
DOI: 10.3389/fpls.2021.660620
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Genomic and Greenhouse Assessment of a Novel Plant Growth-Promoting Rhizobacterium for Tomato Plant

Abstract: Plant growth promoting rhizobacteria (PGPR) can display several plant-beneficial properties, including support to plant nutrition, regulation of plant growth, and biocontrol of pests. Mechanisms behind these effects are directly related to the presence and expression of specific genes, and different PGPR strains can be differentiated by the presence of different genes. In this study we reported a comprehensive evaluation of a novel PGPR Klebsiella variicola UC4115 from the field to the lab, and from the lab to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 64 publications
1
4
0
1
Order By: Relevance
“…Several siderophore genes mediating the plant response against osmotic stress and pathogens have been identified in Pseudomonas species (Kang et al 2020). The detection of siderophore genes, entABCFH, in the genome of S. maltophilia JVB5 agrees with Guerrieri et al (2021) and Hubrich et al (2021), who reported similar genes in the genome of the endophytic bacterium Klebsiella variicola UC4115, with functions in deriving enterobactin from chorismate.…”
Section: Discussionsupporting
confidence: 84%
“…Several siderophore genes mediating the plant response against osmotic stress and pathogens have been identified in Pseudomonas species (Kang et al 2020). The detection of siderophore genes, entABCFH, in the genome of S. maltophilia JVB5 agrees with Guerrieri et al (2021) and Hubrich et al (2021), who reported similar genes in the genome of the endophytic bacterium Klebsiella variicola UC4115, with functions in deriving enterobactin from chorismate.…”
Section: Discussionsupporting
confidence: 84%
“…Some strains produced higher concentration of IAA than the same species in other reports. For example, Klebsiella variicola SSI‐2 produced 152.31 μg ml −1 IAA that was much higher than K. variicola strain UC4115 (68.32 μg ml −1 IAA) (Guerrieri et al ., 2021). Pseudomonas entomophila SSX‐5 produced more IAA (126.98 μg ml −1 ) than P. entomophila CN11 (23.26 μg ml −1 IAA) (Li et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We used whole-genome sequencing and annotation to provide useful insights into the mechanisms governing plant growth. In a previous study, many plant growth-promoting bacteria were analyzed at the whole-genome level to gain an in-depth understanding of PGP mechanisms in bacteria such as Bacillus pumilus strain SF-4 (Iqbal et al 2021a ), B. subtilis BS87 and B. megaterium BM89 (Chandra et al 2021 ), Pseudomonas aeruginosa B18 (Singh et al 2021 ), Klebsiella variicola UC4115 (Guerrieri et al 2021 ), and Streptomyces (Subramaniam et al 2020 ). Many genes have been identified by whole-genome sequencing and have been implicated in direct mechanisms of plant growth (e.g., chitinase, phosphate solubilization, auxin production, iron acquisition, and nitrogen fixation) (Iqbal et al 2021a ; Chandra et al 2021 ; Singh et al 2021 ; Guerrieri et al 2021 ; Subramaniam et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%